The exceptionally high thermal conductivity after 'alloying' two-dimensional gallium nitride (GaN) and aluminum nitride (AlN). (6th January 2021) - Wang, Huimin; Wei, Donghai; Duan, Junfei; Qin, Zhenzhen; Qin, Guangzhao; Yao, Yagang; Hu, Ming
Abstract: Alloying is a widely employed approach for tuning properties of materials, especially for thermal conductivity which plays a key role in the working liability of electronic devices and the energy conversion efficiency of thermoelectric devices. Commonly, the thermal conductivity of an alloy is acknowledged to be the smallest compared to the parent materials. However, the findings in this study bring some different points of view on the modulation of thermal transport by alloying. The thermal transport properties of monolayer GaN, AlN, and their alloys of Ga x Al1− x N are comparatively investigated by solving the Boltzmann transport equation (BTE) based on first-principles calculations. The thermal conductivity of Ga0.25 Al0.75 N alloy (29.57 Wm −1 K −1 ) and Ga0.5 Al0.5 N alloy (21.49 Wm −1 K −1 ) are found exceptionally high to be between AlN (74.42 Wm −1 K −1 ) and GaN (14.92 Wm −1 K −1 ), which violates the traditional knowledge that alloying usually lowers thermal conductivity. The mechanism resides in that, the existence of Al atoms reduces the difference in atomic radius and masses of the Ga0.25 Al0.75 N alloy, which also induces an isolated optical phonon branch around 18 THz. As a result, the scattering phase space of Ga0.25 Al0.75 N is largely suppressed compared to GaN. The microscopic analysis from the orbital projected electronic density of states and the electron localization function further provides insight that the alloying process weakens the polarization of bonding in Ga0.25 Al0.75 N alloy and leads to the increased thermal conductivity. The exceptionally high thermal conductivity of the Ga x Al1− x N alloys and the underlying mechanism as revealed in this study would bring valuable insight for the future research of materials with applications in high-performance thermal management.